Reading and Writing Skills of Slow Learner Students in Hulu Langat Guidance Studio Malaysia - Khoirunisya, Vina; Hidayati, Yulia Maftuhah (Universitas Muhammadiyah Surakarta, 2023)
Purpose: This study analyzes slow learners' reading and writing skills in Hulu Langat Guidance Studio, Malaysia. The research method used is qualitative. The research was conducted at Hulu Langat Guidance Studio, Malaysia, with participants of 35 students and 3 Hulu Langat Guidance Studio teachers. Methodology: The data collection techniques of this research are observation, interview, and documentation. After gathering the data, data analysis will be carried out, starting with data reduction, data presentation, and conclusion drawing. Data validity uses source and method of triangulation. Results: The results of this study showed that, of the 35 students at the Hulu Langat Guidance Studio for reading ability in recognizing letters and reading them as syllables, words, and sentences as well as reading short texts with correct pronunciation and intonation in reading aspects, scores of 13% or very capable, 16% or capable, 25% less capable, and 46% were unable to master both indicators in reading aspects. On the ability to write obtained 21% or very capable, 29% or capable, 33% or less capable, and 17% or not able to master the indicator moves the index finger to create various forms of lines and circles, copy or imitate letters, words, or sentences from books or whiteboards on aspects of writing. Applications/Originality/Value: The difference between this study with previous research lies in the research respondents, research time, measurement tools, literature used, the theory used, and research results.